Examining the hypothesis based learning approach - Semerci, Cetin (Sila Science, 2011)
The aim of this study is to examine the Hypothesis Based Learning Approach. In this study, Hypothesis Based learning and its relation with constructivist and problem based learning was examined. Hypothesis Based learning is learning approach emerged in 2000 by the joint study of the scientist who especially study on Mathematics, computer and language in the United States of America. Hypothesis Based learning is a learning approach which starts with observation, provide learning through the instrument of hypothesis, constructivist based and unites the practice with theory. Hypothesis Based learning has both theory and practice dimension. Students focus on the subject on these dimensions freely. Students learn approaching the subjects like a scientist. But to some students, studying freedom cannot provide benefit; this situation is open to the abuse. If scientific studying approaches were not taught, sufficient learning may not take place. Hypothesis Based activities show important characteristics of constructivist learning and problem based learning.
Keywords: Hypothesis based learning approach; Constructivism; Problem based learning